Analysis of the type of intervention for nutritional improvement in toddlers with poor nutritional status: A literature review - Alfian Fajri Raharunuddin; Hermiaty Nasruddin; Martira Maddeppungeng; Sidrah Darma; Asrini Safitri (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Stunting remains a major nutritional problem in Indonesia and significantly impacts human resource quality. Purpose: to examine various nutritional interventions that influence the reduction of stunting prevalence among toddlers. Method: A literature review was conducted by searching articles from PubMed, Google Scholar, ScienceDirect, and Research Gate. Literature selection was carried out systematically and analyzed narratively. Results: A review of 38 articles showed that supplementation interventions such as SQ-LNS, LNS, and RUSF were the most effective in reducing stunting prevalence by 10–16%, especially when provided to children aged 6–24 months along with nutrition education. Locally based supplementary feeding (PMT) also had a positive effect, particularly when combined with fortification and education. Educational and community-based interventions played an important role in improving compliance and the sustainability of nutrition programs. Conclusion: The combination of nutritional supplementation and education is the most effective strategy for reducing stunting among toddlers.